Scientific and Methodological Basis of Practice-Oriented Training of Students-Biologists: A Case Study in Kazakhstan - Nurgaliyeva, A.; Childibayev, D.; Sagyndykova, S.; Azman, M. N. A.; Saparova, G. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
The aim of this paper is to solve the problem of practical major training for biology majors under the framework of higher education modernization. By using a variety of specialized techniques, forms and teaching methods, a discipline that is not only universal and specialized has been formed, competencies, as well as reflective and professional self-actualization. The aim of this research is to study the practically test the organizational and pedagogical conditions of the practice-oriented training for the future teachers-biologists. This quantitative research is to study the practice-oriented training of student biologist from the literature review. Questionnaire pertaining to the scientific and methodological basis of practice-oriented were send to the 3rd and 4th year students majoring in biology. According to the framework standard, a descriptive analysis of the results is carried out on the respondents' assessment of the professional maturity of future teachers; motivation is a symbolic bundle of professional action motivation (professional orientation, job satisfaction), and the individual is an important characteristic of teachers forming an individual. Willingness, ways of personal self-expression and self-development (professional intent, reflection), and cognition serve as the basis for training subjects, methods, psychology, and teaching skills (vocational training, teaching thinking). The proposed levels of professional readiness of future teachers will help to improve the competency in pedagogy of the biology teacher and contribute to the higher education in term of the education curriculums.